Emerging roles of TRIM27 in cancer and other human diseases - Yu, Chengpeng; Rao, Dean; Wang, Tiantian; Song, Jia; Zhang, Lei; Huang, Wenjie (Frontiers in Cell and Developmental Biology, 2022)
As a member of the TRIM protein family, TRIM27 is a RING-mediated E3 ubiquitin ligase that can mark other proteins for degradation. Its ubiquitination targets include PTEN, IκBα and p53, which allows it to regulate many signaling pathways to exert its functions under both physiological and pathological conditions, such as cell proliferation, differentiation and apoptosis. During the past decades, TRIM27 was reported to be involved in many diseases, including cancer, lupus nephritis, ischemia-reperfusion injury and Parkinson's disease. Although the research interest in TRIM27 is increasing, there are few reviews about the diverse roles of this protein. Here, we systematically review the roles of TRIM27 in cancer and other human diseases. Firstly, we introduce the biological functions of TRIM27. Next, we focus on the roles of TRIM27 in cancer, including ovarian cancer, breast cancer and lung cancer. At the same time, we also describe the roles of TRIM27 in other human diseases, such as lupus nephritis, ischemia-reperfusion injury and Parkinson's disease. Finally, we discuss the future directions of TRIM27 research, especially its potential roles in tumor immunity.